Varicella-Zoster Virus Vasculopathy: The Growing Association Between Herpes Zoster and Strokes. (September 2015) - Powell, David R.; Patel, Shiddhi; Franco-Paredes, Carlos
Abstract : Abstract: Varicella-zoster virus (VZV) is herpes virus that after its reactivation from nerve ganglia to cause herpes zoster may lead to a variety of neurologic complications, including encephalitis, meningitis, retinal necrosis or myelitis. In addition, VZV can spread to arteries in the central nervous system and cause hemorrhagic or ischemic complications due to an inflammatory vasculopathy. In fact, there is a growing epidemiological and clinical recognition that there is an association between VZV reactivation and subsequent strokes. Herein, we present a case of an immune compromised individual with reactivation of VZV causing dermatomal herpes zoster followed by multifocal vasculopathy. We also review the literature to highlight key aspects of VZV-associated vasculopathy.